Developing a cost calculation model for inland navigation. (June 2017) - Al Enezy, Osama; van Hassel, Edwin; Sys, Christa; Vanelslander, Thierry
Abstract: The inland waterway transport sector in Western Europe is a competitive market with an excess of supply over demand. Overcapacity puts pressure on prices, and has caused a decline in profitability, particularly since the economic crisis of 2008. In this competitive environment, it is crucial for ship owners to have accurate information on the cost of their service in order to avoid setting freight rates at non-profitable levels. For this reason, a scientific instrument to calculate the cost of inland waterway transport is needed. Following upon a literature review, the aim of the paper is to develop a new cost calculation model by vessel type, taking into account internal fixed and variable out-of-pocket costs, from the ship owner's perspective, as well as external cost elements of inland waterway transport. Subsequently, the methodology behind the input parameters, the model computations, and the output is discussed and supported with a case study. The paper reveals that a model for use in the inland navigation sector needs to be based on company-specific input parameters. Due to the variety of ship types and dimensions, operation modes, contracts, and specific trip considerations, models based on average values seldom provide accurate results. The collection of averages, however, can serve scientific purposes, such as the analysis of investment decisions, or the effect of changes to the charter agreement. As such, the model proposed in this paper is capable of collecting and processing user input for the generation of average values, for further insights into the inland navigation sector.